APPLICATION OF TURBO CODES IN UNMANNED AERIAL SYSTEMS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
In the modern world, unmanned aerial systems play an extremely important role in the economy, research, environmental protection, and military operations. Unmanned aerial vehicles, as elements of these systems, operate and perform their tasks by transmitting data and commands over communication radio channels that often face harsh conditions and limitations on frequency-time and energy resources. At the same time, the demand for higher quality and accuracy of the information obtained and the commands issued are constantly increasing. The purpose of this research work is to examine and evaluate the potential of using turbo codes for error correction, especially packet codes, in the communication radio channels of unmanned aerial systems. Different types of turbo encoder designs are reviewed, along with their advantages and disadvantages, to assess their applicability for these channels. The importance of interleaving is discussed, and a structure and algorithm for the operation of an interleaver is proposed as an essential element of the turbo encoder design. Finally, conclusions and recommendations are made for directions for further research and the application of turbo codes in unmanned aerial systems.